2021
DOI: 10.3389/fphys.2021.671827
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Capacity in Overweight and Obese Children and Adolescents: A Cross-Sectional Study

Abstract: Background: One of the objective methods of assessing the level of cardiopulmonary capacity in overweight and obese children and adolescents is cardiopulmonary exercise testing (CPET).Aims: The purpose of present study is an evaluation of aerobic capacity in high body mass index (BMI) children and adolescents by comparing them with a normal weight control group by CPET.Methods and Procedures: The subjects were recruited from participants of the Program of Treatment for Overweight and Obese Children organized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…This data strengthens our findings, which are novel due to the young adolescent age of the case participant. Significant differences in cardiorespiratory fitness have been found in children and adolescents when comparing those with normal weight to those with obesity ( 16 ). Usually, these studies focus on peak V̇O 2 as the primary outcome and do not assess for abnormal patterns that may reveal disease states, as we did in ours.…”
Section: Discussionmentioning
confidence: 99%
“…This data strengthens our findings, which are novel due to the young adolescent age of the case participant. Significant differences in cardiorespiratory fitness have been found in children and adolescents when comparing those with normal weight to those with obesity ( 16 ). Usually, these studies focus on peak V̇O 2 as the primary outcome and do not assess for abnormal patterns that may reveal disease states, as we did in ours.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, little is known regarding the association of overweight/obesity with CRF, namely VO 2 max. In 2021, Grzyb et al have shown that children and adolescents with obesity demonstrated similar VO 2 max values compared to those with overweight, but significantly greater than children of normal weight [ 54 ]. There is evidence that augmentation of VO 2 max in adults is related to lower FM and WC [ 8 , 9 , 10 ], but in the case of children, data are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The possible covariates contained age, gender, race, educational level, BMI (kg/m 2 ), waist circumference (cm), poverty-to-income ratio, household smoke exposure, family history of asthma, total energy (kcal), vitamin C intake (mg/1,000 kcal), vitamin E intake (mg/1,000 kcal), zinc intake (mg/1,000 kcal), selenium intake (μg/ 1,000 kcal). Overweight was defined as a BMI for age and gender over the 85th according to the World Health Organization Growth Reference in this study [18]. The intake of all nutrients was calculated by adding up the dietary and supplemental intakes in this study.…”
Section: Covariatesmentioning
confidence: 99%